2018
DOI: 10.1093/aje/kwy143
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Maternal Exposure to Dichlorodiphenyltrichloroethane and Pyrethroids With Birth Outcomes Among Participants in the Venda Health Examination of Mothers, Babies and Their Environment Residing in an Area Sprayed for Malaria Control

Abstract: Although effective in controlling malaria, Indoor Residual Spraying results in elevated exposure to insecticides such as dichlorodiphenyltrichloroethane (DDT) and pyrethroids. These chemicals cross the placenta but no studies have examined their associations with birth outcomes in populations residing in indoor residual spraying areas. We investigated this question in the Venda Health Examination of Mothers, Babies and their Environment (VHEMBE), a birth cohort study of 751 South African children born between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…Overall, despite the ubiquity of their use, few epidemiologic investigations have been conducted on the relation between fetal exposure to pyrethroids and growth in early childhood besides work conducted in this cohort 14 , 18 . Moreover, conflicting evidence for the influence of pyrethroids on birth characteristics 12 , 13 , 15 18 and child size 14 , 19 predominate. Studies in our cohort have several notable differences and advantages over past work including larger sample size, use of biomarkers of exposure (i.e., pyrethroid metabolite concentrations), and longer follow-up.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Overall, despite the ubiquity of their use, few epidemiologic investigations have been conducted on the relation between fetal exposure to pyrethroids and growth in early childhood besides work conducted in this cohort 14 , 18 . Moreover, conflicting evidence for the influence of pyrethroids on birth characteristics 12 , 13 , 15 18 and child size 14 , 19 predominate. Studies in our cohort have several notable differences and advantages over past work including larger sample size, use of biomarkers of exposure (i.e., pyrethroid metabolite concentrations), and longer follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous work in a rural South African birth cohort with high exposure to pyrethroids and DDT suggests associations between prenatal exposure to insecticides and early child size. We found that prenatal exposure to DDT and dichlorodiphenyl dichloroethylene (DDE, a DDT breakdown product) was associated with greater birth size (birth weight, length, and head circumference) 18 and larger weight-for-age at 1 and 2 years among girls 14 . In contrast, maternal urine concentrations of several pyrethroid metabolites were associated with lower weight-forage at 1 and 2 years, especially among boys.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…He reported that IRS was associated with elevated serum DDT/DDE and urinary pyrethroid metabolite concentrations in peripartum samples collected from 751 VHEMBE women 24,25 . Associations between maternal exposure to DDT and hypertensive disorders of pregnancy 26 , larger birth size 27 , and higher body composition measures, and marginally altered motor development were found among VHEMBE girls at age 1 and/or 2 years 28 . Prenatal exposure to pyrethroids was also associated with lower body composition measures among boys 28 and altered motor development among girls aged 1 to 3.5 years 29,30 .…”
Section: Nutrition and Toxicodietary Exposuresmentioning
confidence: 84%
“…In many countries, including South Africa, DDT has been used for decades (Mabaso et al, 2004), resulting in elevated body burdens of DDT and its breakdown product dichlorodiphenyldichloroethylene (DDE) in individuals living in sprayed homes (Gaspar et al, 2017). Concerns have been raised regarding the potential health effects related to exposure to these chemicals, especially in developing children (Bouwman and Kylin, 2009; Chevrier et al, in press; Coker et al, 2018; Eskenazi et al, 2009; Huang et al, in press). …”
Section: Introductionmentioning
confidence: 99%